Variogram-based evaluations of DXA correlate with vertebral strength, but do not enhance the prediction compared to aBMD alone. (22nd August 2018) - Dong, Xuanliang Neil; Lu, Yongtao; Krause, Matthias; Huber, Gerd; Chevalier, Yan; Leng, Huijie; Maquer, Ghislain
Abstract: Ancillary evaluation of spinal Dual-energy X-ray Absorptiometry (DXA) via variogram-based texture evaluation (e.g., Trabecular Bone Score) is used for improving the fracture risk assessment, despite no proven relationship with vertebral strength. The purpose of this study was thus to determine whether classical variogram-based parameters (sill variance and correlation length) evaluated from simulated DXA scans could help predicting the in vitro vertebral strength. Experimental data of thirteen human full vertebrae (i.e., with posterior elements) and twelve vertebral bodies were obtained from two existing studies. Areal bone mineral density (aBMD) was calculated from 2D projection images of the 3D HR-pQCT scan of the specimens mimicking clinical DXA scans. Stochastic predictors, sill variance and correlation length, were calculated from their experimental variogram. Vertebral strength was measured as the maximum failure load of human vertebrae and vertebral bodies from mechanical tests. Vertebral strength correlated significantly with sill variance (r = 0.727) and correlation length (r = 0.727) for the vertebral bodies, and with correlation length (r = 0.593) for full vertebrae. However, the stochastic predictors improved the strength prediction made by aBMD alone by only 11% for the vertebral bodies while no improvement was observed for the full vertebrae. Despite a correlation, classical variogram parameters such as sill variance and correlation length do not enhance the prediction of in vitro vertebral strength beyond aBMD. It remains unclear why some variogram-based evaluations of DXA improve fracture prediction without a proven relationship with vertebral strength.